2016
DOI: 10.1016/j.cemconres.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-sealing of cracks in concrete using superabsorbent polymers

Abstract: 5Cracks in concrete can self-heal when exposed to prolonged wetting, but this is limited to narrow cracks. In 6 practice, cracks > 0.2mm cause leakage and impair performance of structures. The potential of 7 superabsorbent polymers (SAP) to self-seal such cracks was investigated via transport experiments, 8 microscopy and modelling. Forty samples containing SAP and through-thickness cracks were subjected to 9 0.12wt.%NaCl at 4m/m pressure gradient to simulate groundwater seepage. Results show that SAP can re-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(131 citation statements)
references
References 26 publications
(2 reference statements)
2
125
1
3
Order By: Relevance
“…Studies have reported on SAP-induced changes in cement composite properties after Jensen et al proposed SAP as a water-entraining admixture for internal curing in high-performance concrete [1,2]. It has been reported that SAPs can reduce the permeability of water through cracks when cracks occur in cement composites [3,4,5,6]. It also has been reported that SAPs heal cracks by supplying moisture to cement composites [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported on SAP-induced changes in cement composite properties after Jensen et al proposed SAP as a water-entraining admixture for internal curing in high-performance concrete [1,2]. It has been reported that SAPs can reduce the permeability of water through cracks when cracks occur in cement composites [3,4,5,6]. It also has been reported that SAPs heal cracks by supplying moisture to cement composites [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the latest studies focused on tackling autogenous shrinkage occurring in high-performance cement-based materials with a low water-to-binder ratio as SAPs can serve as internal reservoirs to supply extra curing water to drying areas (so called "internal curing"), particularly caused by self-desiccation [1,[7][8][9][10][11]. Other works performed include the effects of SAP additions on mechanical properties [8,[12][13][14][15], rheological properties [16][17][18], self-sealing [19][20][21][22] and self-healing [23], early-age restrained cracking [12,24], creep [25,26], thermal coefficient [27], and freeze-thaw resistance [16,28,29]. The findings were not quite different among the studies: (1) additions Polymers 2017, 9, 600 2 of 14 thermal coefficient [27], and freeze-thaw resistance [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Within this research area, different mechanisms are under development. The most common ones use encapsulated polymers (Dry and McMillan 1996;Thao et al 2009;Van Tittelboom et al 2011), calcium carbonate precipitating bacteria (Wiktor and Jonkers 2011;Van Tittelboom et al 2010;Wang et al 2012), or embedded hydrogels (Dennis Lee et al 2010;Kim and Schlangen 2010;Snoeck et al 2013) as healing/sealing agents. The current paper describes a preliminary study to evaluate whether alkaline activators can be used as healing agents in order to obtain self-healing in special types of concrete such as those containing large amounts of unhydrated fly ash (FA) or blast-furnace slag (BFS) particles.…”
Section: Introductionmentioning
confidence: 99%